Peran Media Audio-Visual dalam Mendukung Pembelajaran Bahasa Kedua Pada Konten 'Johny Johny Yes Papa’ - Hemas Haryas Harja Susetya; Mochamad Ighfir Sukardi; Warda Lathifah (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examines the impact of the Johny Johny Yes Papa song on YouTube on early childhood English vocabulary acquisition. The purpose of this research is to analyze vocabulary improvement through engaging audio-visual exposure. Using a descriptive qualitative approach, the study employs participant observation, parent interviews, and content analysis. The findings indicate that children who frequently watch this content are able to imitate words such as